Adam Badeau correspondence - Badeau, Adam, 1831-1895.
Correspondence relating to Ulysses S. Grant, whom Badeau served as military secretary (1864-1869), his writings about Grant, and Badeau's social engagements in London. Includes copies of letters (1864-1868) written by Grant. Correspondents include Orville E. Babcock, Rutherford B. Hayes, Andrew Johnson, Emory Upton, and Fernando Wood.
In part, transcripts.
Army officer, author, and diplomat.
Collection material in English, with French.
Keywords: Babcock, Orville Elias, -- 1835-1884 -- Correspondence; Grant, Ulysses S. -- 1822-1885.; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Johnson, Andrew, -- 1808-1875 -- Correspondence; Upton, Emory, -- 1839-1881 -- Correspondence; Wood, Fernando, -- 1812-1881 -- Correspondence; London (England) -- Social life and customs; Army officers; Authors; Diplomats